2013
DOI: 10.1371/journal.pone.0061705
|View full text |Cite|
|
Sign up to set email alerts
|

UGT74D1 Is a Novel Auxin Glycosyltransferase from Arabidopsis thaliana

Abstract: Auxin is one type of phytohormones that plays important roles in nearly all aspects of plant growth and developmental processes. The glycosylation of auxins is considered to be an essential mechanism to control the level of active auxins. Thus, the identification of auxin glycosyltransferases is of great significance for further understanding the auxin regulation. In this study, we biochemically screened the group L of Arabidopsis thaliana glycosyltransferase superfamily for enzymatic activity toward auxins. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 49 publications
3
66
0
Order By: Relevance
“…However, OxIAA was not investigated as a naturally occurring substrate (Jin et al 2013). To investigate directly if UGT74D1 exhibits glucosyltransferase activity against OxIAA, we expressed glutathione S -transferase (GST) fused with UGT74D1 (GST–UGT74D1) in E. coli for use in an enzyme assay.…”
Section: Resultsmentioning
confidence: 99%
“…However, OxIAA was not investigated as a naturally occurring substrate (Jin et al 2013). To investigate directly if UGT74D1 exhibits glucosyltransferase activity against OxIAA, we expressed glutathione S -transferase (GST) fused with UGT74D1 (GST–UGT74D1) in E. coli for use in an enzyme assay.…”
Section: Resultsmentioning
confidence: 99%
“…UDP-glycosyltransferases are enzymes capable of adding a glucose molecule to a set of molecular targets, including hormones. Indeed, the UDP-glycosyltransferases UGT84B1, UGT74E2, and UGT74D1 can all add sugar molecules to auxins, in particular, IAA and indole-3-butyric acid, and may thereby alter the activity, solubility, and cellular localization of auxin (Jackson et al, 2001;Tognetti et al, 2010;Jin et al, 2013). As phyllotaxis is tightly dependent on auxin accumulation and transport (Reinhardt et al, 2003;Jönsson et al, 2006;Smith et al, 2006), TEC3 may therefore contribute to the control of auxin homeostasis in the shoot apical meristem.…”
Section: Discussionmentioning
confidence: 99%
“…Another A. thaliana enzyme, AtUGT74E2 preferred IBA, NAA, JA, and 2-4 D more than IAA for glucosylation, as reported by Tognetti et al (2010). Recently, Jin et al (2013) have identified the UGT74D1 that catalyzes predominantly synthesis of IBA-and IPA-glucose, but is also able to conjugate IAA and NAA.…”
Section: Iaglc Synthase Specifically Glucosylates Indole-3-acetic Acidmentioning
confidence: 70%
“…The biological significance of glucosyltransferases synthesizing conjugates of various auxins is an intriguing problem. It cannot be excluded that diversity of these enzymes is associated with the functional redundancy as proposed by Jin et al (2013). On the other hand, the occurrence of glucosyltransferases with a broad substrate preference may be a result of different expression pattern of UGT genes during plant development.…”
Section: Peamentioning
confidence: 99%
See 1 more Smart Citation